2004
DOI: 10.1038/sj.npp.1300475
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Citalopram and Escitalopram on 5-Ht-Mediated Neuroendocrine Responses

Abstract: Acute oral administration of selective serotonin re-uptake inhibitors (SSRIs) increases plasma cortisol by facilitating brain serotonin activity. Recently, salivary cortisol sampling has grown in popularity as a noninvasive means of assessing HPA axis activity. The aim of the present study was to find out whether acute oral administration of the SSRI, citalopram, increases salivary cortisol in healthy volunteers and whether the increase produced by an equivalent dose of its active isomer, escitalopram, is grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
3
31
2
1
Order By: Relevance
“…This is true both in preclinical studies measuring serotonin release with microdialysis [20] and in indirect measures in human volunteers employing, for example, the increase in salivary cortisol as an indirect index of enhanced serotonin activity [21]. In a task of emotional processing, we found that a single dose of the SSRI, citalopram (20 mg), increased the recognition of happy facial expressions [22].…”
Section: (B) Antidepressants and Emotional Processingmentioning
confidence: 75%
“…This is true both in preclinical studies measuring serotonin release with microdialysis [20] and in indirect measures in human volunteers employing, for example, the increase in salivary cortisol as an indirect index of enhanced serotonin activity [21]. In a task of emotional processing, we found that a single dose of the SSRI, citalopram (20 mg), increased the recognition of happy facial expressions [22].…”
Section: (B) Antidepressants and Emotional Processingmentioning
confidence: 75%
“…Analysis of blood pressure was carried out using ANOVA with factors 'treatment' and 'time' (t ¼ 0 h or t ¼ 210 or t ¼ 285 min) of systolic and diastolic blood pressure separately. As escitalopram is known to increase cortisol levels (Nadeem et al, 2004), a planned comparison between cortisol levels in the two treatment groups at t ¼ 210 and t ¼ 285 min was performed with a paired samples Student's t-test. Furthermore, to test whether serum levels of escitalopram were constant during psychophysiological testing, a paired samples Student's t-test was performed to compare the levels at t ¼ 210 min and t ¼ 285 min.…”
Section: Discussionmentioning
confidence: 99%
“…To monitor the effects of escitalopram, physiological (blood pressure), biochemical (serum escitalopram), and endocrine (serum cortisol) assessments were performed. As escitalopram is known to increase cortisol (Nadeem et al, 2004), an increase in the plasma level of this hormone was expected. Blood pressure was monitored, as orthostatic hypotension is one of the listed side effects of escitalopram.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in healthy volunteers have demonstrated that intravenous (IV) citalopram (at doses of 5, 10 or 20 mg) stimulates significant increases in both plasma and salivary cortisol and plasma prolactin levels (Seifritz et al 1996(Seifritz et al , 1997Kapitany et al 1999;Attenburrow et al 2001;Bhagwager et al 2002). The effects of acute oral (PO) administration of clinical doses of citalopram (20 and 40 mg) on these neuroendocrine responses are not as remarkable, but modest increases in plasma cortisol have been described (Henning and Netter 2002;Nadeem et al 2004;Hawken et al 2006). Measurable increases in plasma prolactin, however, have not been observed to date following PO administration of these doses (Henning and Netter 2002;Nadeem et al 2004;Hawken et al 2006).…”
Section: Introductionmentioning
confidence: 95%
“…The effects of acute oral (PO) administration of clinical doses of citalopram (20 and 40 mg) on these neuroendocrine responses are not as remarkable, but modest increases in plasma cortisol have been described (Henning and Netter 2002;Nadeem et al 2004;Hawken et al 2006). Measurable increases in plasma prolactin, however, have not been observed to date following PO administration of these doses (Henning and Netter 2002;Nadeem et al 2004;Hawken et al 2006). Using a larger (30-60 mg) PO dose range of citalopram, Flory et al (2004) did, however, report a modest rise in prolactin levels in approximately one third of subjects.…”
Section: Introductionmentioning
confidence: 98%